2008
DOI: 10.1371/journal.pone.0003751
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Based Detection Tests for the Diagnosis of Helicobacter pylori Infection in Children: A Meta-Analysis

Abstract: BackgroundNumerous serologic tests are available for the diagnosis of H. pylori infection in children. Common designs of antibody-based detection tests are ELISA and Western Blot (WB). For developing countries with limited laboratory resources and access, ELISA would be the preferred method because of its simplicity, lower cost and speed. Although in adults ELISA has proven to be highly accurate in diagnosing H. pylori infection; in children, it has shown variable accuracy.Methods/FindingsWe conducted a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 99 publications
2
60
0
1
Order By: Relevance
“…3,5 However, marked differences in H. pylori seroprevalence have been observed and reported among various ethnic and racial groups from other studies. 17 In this study it was confirmed that HP prevalence in children was significantly higher if family members were also HP infected regardless of other socioeconomic and environmental factors.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…3,5 However, marked differences in H. pylori seroprevalence have been observed and reported among various ethnic and racial groups from other studies. 17 In this study it was confirmed that HP prevalence in children was significantly higher if family members were also HP infected regardless of other socioeconomic and environmental factors.…”
Section: Discussionmentioning
confidence: 96%
“…2 HP infection is one of the most common bacterial infections in humans affecting nearly 50% of the world's population. 3 It is usually acquired in childhood and is associated with sociodemographic factors such as low socio-economic status, poor hygiene, and overcrowding. 4 The prevalence of HP infection is markedly high in developing countries, Acute infection is often silent, with symptoms and disease manifesting later in life, as does an increased risk of gastritis, peptic ulcer and HP related malignancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among suggested associations is exposure to tobacco smoke (Arnold et al, 2011;Hancox et al, 2004;Laszewicz et al, 2014;Moayyedi et al, 2002;Roesler et al, 2014;Wang et al, 2012), quality of indoor conditions (Laszewicz et al, 2014), quality of environment (Hancox et al, 2004;Krumbiegel et al, 2000;Roesler et al, 2014;Rothenbacher et al, 1998;Vasar et al, 2011;Wang et al, 2012;Wex et al, 2010), genetic and race influences (10,17,22,26,29,32), social-economic effects and education (Amedei et al, 2010;Bode et al, 2002;Chen and Blaser, 2008;Hancox et al, 2004;Laszewicz et al, 2014;Leal et al, 2008), exposure to allergens from domestic animals (Amedei et al, 2010) and lately the exposure to nanoparticles from car exhausts, mainly with diesel engines (Amedei et al, 2010). Another theory speculates about the possibility that the use of antibiotics given either therapeutically or in small amounts in food influences composition of the microbiome and triggers the allergies (Arnold et al, 2011, Blaser 2012Fu 2014;Holster et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo experiments in humans have shown elevated levels of interleukin-1b (IL-1b) and interleukin-8 (CXCL8), among others, and have demonstrated that monocytes and polymorphonuclear cells are recruited early during infection, followed by lymphocyte infiltration after 4 weeks [7]. In the clinic, the determination of total immunoglobulin G (IgG) titres against whole extracts or particular antigens has been in use for several years, greatly improving the understanding of infection dynamics [8].…”
Section: Introductionmentioning
confidence: 99%